Clinical Characteristics, Pathological Features and Treatment Outcomes of Children With Nephrotic Syndrome at Princess Marina Hospital, Botswana - Thembisile Dintle Mosalakatane MBBS; Errol Gottlich Cert Nephrology (SA) Paed; Loeto Mazhani MD; Dipesalema Joel MRCPI; Thabiso Vivien Mogotsi MBChB; Tonya Arscott-Mills MD (Global Pediatric Health, 2024)
Objective. Despite the remarkable progress made in the understanding and treatment of childhood nephrotic syndrome (NS), a lot is still unknown about its epidemiology in many African countries. This study sought to determine the clinicopathological features and treatment outcomes of children with NS at the largest tertiary hospital in Botswana. Methods. A retrospective study of 26 children with NS treated from 2009 to 2014 was conducted. Results. Mean age at presentation was 5.96 ± 3.06. Hematuria was found in 92.3%, low C3 in 26.7%, high creatinine in 19.2% and hypertension in 46.2% of the patients. 92.3% had primary NS out of which 23.1% had familial NS. HIV, tuberculosis and hepatitis B infections were diagnosed in 3.85%, 9.09% and 4.16% respectively. 69.2% had steroid-resistant nephrotic syndrome, focal segmental glomerulosclerosis (SRNS-FSGS). Conclusion. The frequency of primary SRNS-FSGS and familial SRNS appears to be much higher in Botswana highlighting the possibility of genetic causes.